Design And Development Of A Multimode Cricket Bowling Machine - Davaraj, Fernandez Dhanaraj (2017)
This research was about the development of a multimode cricket bowling machine. The purpose of the machine was to emulate the ball deliveries of real cricket bowlers during training. Furthermore, the machine could execute continuous ball deliveries for the batsmen when the bowlers are not available. Besides that, past studies had not disclosed some of criteria related to the development of the bowling machine such as effects of wet ball on velocity and speed relationship between the ball and the wheels. In response, a multimode cricket bowling machine was fabricated and its performance analysed. Based on the kinematics of the bowling deliveries, the design requirements of the machine were made prior to fabrication. As for the control system, a rule-based microcontroller system was constructed to change the wheel’s angular speed. The three major experiments for analysing the performance were ball velocity, distance, and spin. Experimental results showed that ball velocities were 17.53 m/s and 19.78 m/s under slow and medium speed mode with best wheel pressure of 6.25 psi on both wheels. The data consistency was compared using coefficient of variation (COV). From the velocity results, the speed ratio between the ball’s translational velocity and wheel’s linear velocity was obtained. Due to the steep speed ratio gradient, the ball velocity declined after the wheels achieved an angular speed of 2000 rpm at 6.25 psi. Moreover, the trajectory results of the mathematical model simulated was comparable to the measured ball length with error of 0.67 %, 9.31 %, and 12.49 % for slow-horizontal, medium-horizontal, and medium-rolled tests respectively. For the ball spin experiments, the speed ratio equation was used to estimate the ball spin rate with 12.32 % error. Based on the estimation, the ball spin rate decreased as the wheel’s angular speed increased. Furthermore, simulations for the ball trajectory with spin applied were conducted and analysed. The simulations had shown that the ball spin produced ball trajectory effects in line with the implemented rule-based system but the magnitude of the effects was low due to the speed ratio relationship and also the initial ball release angle from the horizontal plane.